Kinerja Auditor dalam Perspektif Komitmen Organisasi dan Stres Kerja: Dimoderasi Locus of Control - Rialdy, Novien; Sari, Maya; Pohan, Mukmin (JURNAL ILMIAH MANAJEMEN & BISNIS, 2025)
Purpose – This study examines the effect of organisational commitment and work stress on auditor performance with locus of control as a moderating variable in the Islamic banking industry in Medan.Methodology – This study employed a quantitative approach to objectively measure the relationships between variables using numerical data. Data analysis was conducted using Partial Least Squares Structural Equation Modelling (PLS-SEM), which is suitable for complex models and relatively small sample sizes. The population consisted of internal auditors from banking companies in Medan, North Sumatra. A total of 115 respondents were selected using purposive and snowball sampling to ensure relevance to the study objectives. Data were collected through a Likert-scale questionnaire to obtain measurable and statistically analyzable information. Findings – The results show that organisational commitment has a positive and significant effect on auditor performance, while work stress has a negative and significant effect on auditor performance. Furthermore, locus of control cannot moderate the effect of organisational commitment on auditor performance, but can moderate the effect of work stress on auditor performance in the Islamic banking industry in Medan.Originality/Novelty – The originality of this study lies in the integration of locus of control as a psychological variable in the structural relationship model between organisational and individual factors on auditor performance.Implications - The implications of this study contribute to management in designing human resource development strategies that take into account the psychological aspects of individuals in improving auditor performance.